2008
DOI: 10.1080/10498850801937208
|View full text |Cite
|
Sign up to set email alerts
|

Research Issues in Inactivation ofListeria monocytogenesAssociated with New Zealand Greenshell Mussel Meat (Perna canaliculus) Using High-Pressure Processing

Abstract: New Zealand Greenshell mussels are currently shucked by heat processing, and this can be used as a listericidal step. Shucking by high pressure processing (HPP) has potential benefits in product quality and increased yield, but processors need to understand the effects of this technology on the safety of their product with respect to Listeria monocytogenes. L. monocytogenes was mixed with minced mussel meat, and 2 g samples (in foil pouches) were subjected to HPP at various pressures, times, and temperatures. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…Table 3 (transesterification reaction) shows the differences between the calculated arithmetic average temperature and the effective temperature for reaction time of 20 and 100 s. It is obvious that only when reaction time excessively exceeds the transient heating time, the two temperatures become close to each other. (Fletcher et al 2008) temperature (UHT, 140°C) of liquid food such as milk (Ramaswamy and Marcotte 2006). The pre-heating and cooling periods cannot be ignored as they are significant compared to the holding period.…”
Section: Results Based On Work Published In the Literature On Differementioning
confidence: 99%
See 1 more Smart Citation
“…Table 3 (transesterification reaction) shows the differences between the calculated arithmetic average temperature and the effective temperature for reaction time of 20 and 100 s. It is obvious that only when reaction time excessively exceeds the transient heating time, the two temperatures become close to each other. (Fletcher et al 2008) temperature (UHT, 140°C) of liquid food such as milk (Ramaswamy and Marcotte 2006). The pre-heating and cooling periods cannot be ignored as they are significant compared to the holding period.…”
Section: Results Based On Work Published In the Literature On Differementioning
confidence: 99%
“…A typical temperature profile during HPP treatment is shown in Fig. 8 (Fletcher et al 2008). The rapid increase in the sample temperature during pressurisation is due to compression.…”
Section: High Pressure Processingmentioning
confidence: 99%
“…4.8 , Cruz et al 2008c ). Fletcher et al ( 2008 ) indicated that shucking of New Zealand Greenshell mussels ( Perna canaliculus ) by HPT (400 MPa) has potential benefi ts in product quality, increased yield, and inactivation of Listeria monocytogenes .…”
Section: Oystersmentioning
confidence: 99%
“…Other work has investigated the thermal inactivation of histamine-producing bacteria [78,83], but because Listeria is more heat resistant to thermal inactivation and may also be present in products that cause histamine poisoning, heat processes predicted to eliminate L. monocytogenes are recommended for heat processing seafood [76,84]. The Bigelow model has also been applied to determine the effectiveness of marinades [77] and high pressure processing (HPP) at 400 MPa [85] to inactivate L. monocytogenes (Fig 20.2). Although microbial inactivation is often not log linear, all the available models for thermal inactivation of bacteria in seafood use log linear models of inactivation.…”
Section: Predicting Inactivationmentioning
confidence: 99%